The relevance of Early Church history in the implementation of the great commission in the present era and implications for Christian education in Indonesia - Andrian, Tonny (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
The history of the early church illustrates to the church today the spirit and courage of the early church and the apostles in carrying out the Great Commission. The purpose of this study is to discover the spirit and courage of the early church in carrying out the Great Commission and to invite the church today to carry out this task for the growth of the church. The method used in this research is the qualitative method. The result of this study is that the early church was more conspicuous in carrying out the Great Commission even though it faced heavy challenges but remained brave and resolute. Whereas the church today is still lacking in carrying out the Great Commission there are still many tribes who have not heard the gospel.